Engineering JADEX agents with the MaSE methodology - Mohamad, Radziah; Deris, Safaai; H. Ammar, Hany (2006)
Agent Oriented Software Engineering (AOSE) is one of the fields of the agent domain with a continuous growing interest. The reason is that the possibility to easily specify and implement agent-based systems is of a great importance for the recognition of the add-value of the agent technology in many application fields. In this paper we present an attempt towards this direction, by proposing a kind of roadmap of how one can combine the MaSE methodology for agent-oriented analysis and design and JADEX, a FIPA compliant agent development framework, for an easier analysis, design and implementation of multi-agent systems. Our objective is realized through the presentation of the analysis, design and implementation phases, of a water treatment plant information management system.